INVESTIGATING CHINESE EFL STUDENTS’ PERCEPTIONS OF WRITING PROMPTS OF DIFFERENT AMOUNTS OF INFORMATION - Su You (English Review: Journal of English Education, 2015)
Abstract: This study aims to explore how Chinese EFL students perceive the advantages and disadvantages of prompts providing different amount of information, namely prompt with more information and prompt with less information. Both qualitative and quantitative data were collected through questionnaire survey and semi-structured interview. Research results indicate that: 1) Respondents hold a mixed attitude towards the prompt effect on their task accomplishment. 2) Students believe that prompt type can affect their expression in writing; 3) Students generally agree that prompt with more information facilitate their writing in terms of content and organization; 4) Students’ preference for the prompt type differs across different English proficiency level.Keywords: prompt effect, English writing, testing writing, perceptions